Metaphoric and metonymic motivation in the Light Verb Construction with GIVE - Kopeć, Zbigniew; Guerrero Medina, Pilar (Complutense Journal of English Studies, 2025)
This article demonstrates that the English Light Verb Construction (henceforth LVC) with GIVE is motivated by generic-level metaphors and metonymies. Following Brugman (2001) and Cetnarowska (2012, 2014), LVCs are defined based on criteria that are notably less restrictive than those outlined by Dixon (2005) and Wierzbicka (1982). The study examines the GIVE LVC as a representative case to illustrate the broader pattern of metaphor-driven LVCs. In an LVC, the light verb evokes the source domain of a conceptual metaphor, while its nominal complement indicates the target domain. Thus, in the GIVE LVC, GIVE evokes the transfer schema. This schema, serving as the source domain of metaphors, is mapped onto the conceptual structures underlying the nominal complements of the light verb. Since event schemas represent distinct types of situations, each characterized by unique configurations of thematic roles, metaphoric mappings occur between these roles. However, in the absence of generic-level metonymies, such metaphoric mappings would not be viable. The Correlation Principle (Ruiz de Mendoza and Santibáñez 2003) and the Mapping Enforcement Principle (Ruiz de Mendoza 2005) facilitate metonymic mappings within the target domain, ensuring that conceptual projection from source to target remains systematically constrained.